Impact of tax incentives for educational institutions on access to education in Georgia - Lezhava, Mamuka; Shengelia, Lolita (International Journal Of Management And Economics Invention, 2022)
Sustainable development of the country is ensured by the establishment of a quality and affordable education system. The best formula for overcoming social or economic problems is to achieve inclusive education, which implies the principles of equality and accessibility in the process of receiving education. Access to education on a one hand depends on pricing policies. In the presence of low prices, the individual is motivated to master education and to contribute to the creation of state wealth by realizing his abilities. In the presence of high taxes, the end consumer makes the product more expensive and reduces its consumption. The purpose of the research was to determine the availability of high education in Georgia, in terms of tax benefits in the education sector. It was found that public or private sectors working in the field of education in Georgia enjoy significant benefits. It should be noted that the business of the education sector is exempt from value-added tax, which is the largest tax in Georgia and amounts to 18%. The study found that the use of tax breaks plays an important role in universal access to education. In the presence of high tuition fees, a certain segment of students would no longer be able to continue their studies. All this hinders the economic development of Georgia, as young people between the ages of 25 and 35 leave Georgia as cheap job seekers in neighboring countries and mainly in Europe.